2007
DOI: 10.1016/j.psyneuen.2006.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of verbal and spatial memory changes from moderate to supraphysiological increases in serum testosterone in healthy older men

Abstract: Background-It has been suggested that cognitive changes in response to T supplementation may occur within an ideal range. The objective of this study was to compare the cognitive responses of older, eugonadal men in whom moderate or large increases in serum testosterone levels was induced by exogenous testosterone supplementation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
85
1
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(97 citation statements)
references
References 39 publications
6
85
1
4
Order By: Relevance
“…A cross-sectional study for example showed a positive correlation with T levels in men [17]. Similarly, T has been shown to improve spatial abilities in hypogonadal men or patients with Alzheimer's disease [18][19][20]. Conversely, other studies in hypogonadal men supplemented with T showed no effects on cognitive abilities [21].…”
Section: Discussionmentioning
confidence: 98%
“…A cross-sectional study for example showed a positive correlation with T levels in men [17]. Similarly, T has been shown to improve spatial abilities in hypogonadal men or patients with Alzheimer's disease [18][19][20]. Conversely, other studies in hypogonadal men supplemented with T showed no effects on cognitive abilities [21].…”
Section: Discussionmentioning
confidence: 98%
“…11 Findings from randomized, placebocontrolled clinical trials of testosterone supplementation in older or hypogonadal men show variable cognitive effects. [31][32][33][34][35][36][37][38][39] METHODS A review was conducted through PubMed to identify studies investigating the cognitive effects of ADT. The search words 'androgen deprivation therapy, cognition, memory, imaging' were used to search for articles.…”
Section: Evidence For Cognitive Effects Of Testosteronementioning
confidence: 99%
“…However, the association is far from being clear. Studies found testosterone to improve spatial abilities in hypogonadal men or patients with Alzheimer disease [17]. Androgen levels decline with aging.…”
Section: Discussionmentioning
confidence: 99%